Epidemiology of COVID-19 in the Kingdom of Saudi Arabia: An Ecological Study - Alyami, Mohammad H.; Naser, Abdallah Y.; Orabi, Mohamed A. A.; Alwafi, Hassan; Alyami, Hamad S. (Frontiers in Public Health, 2020)
Objectives: Considering the transmissible nature of COVID-19 it is important to explore the trend of the epidemiology of the disease in each country and act accordingly. This study aimed to examine the trend of COVID-19 epidemiology in the Kingdom of Saudi Arabia in term of its incidence rate, recovery rate, and mortality rate. Material and Methods: We conducted an observational study using publicly available national data taken from the Saudi Ministry of Health for the period between 3 March and 7 June 2020. The number of newly confirmed cases, active cases, critical cases, percentage of cases stratified by age group [adults, children, and elderly] and gender were extracted from the reports of the Saudi Ministry of Health. Results: During the study period, the total number of confirmed cases with COVID-19 rose from one on 2 March 2020 to 101,914 on 7 June, representing an average of 1,039 new cases per day, [trend test, p < 0.000]. Despite the increase in the number of newly confirmed daily cases of COVID-19, the number of reported daily active cases started to stabilize after 2 months from the start of the pandemic in the country and the overall recovery rate was 71.4%. The mortality rate decreased by 6.4% during the study period. COVID-19 was more common among adults and males compared to other demographic groups. Conclusion: The epidemiological status of COVID-19 in the Kingdom of Saudi Arabia showing promising improvement. Males and adults accounted for the majority of COVID-19 cases in the KSA. Further studies are recommended to be conducted at the patient level to identify other patient groups who are at higher risk of getting infected with COVID-19, and for whom the best pharmacological intervention could be provided.